Performance Evaluation of a Commercial-Scale Sulfur Hexafluoride (SF6) Thermal Destruction Process - Mi-Yeong Kim; Joong-Won Lee; Ji-Ho Ahn; Young-Hwan Byun; Su-Bin Yun (Journal of Chemical Engineering of Japan)
Recently, the importance of carbon neutrality has been highlighted, and the power industry is also making efforts to reduce the use of SF6, which is mainly used in power facilities. As part of this, the Korea Electric Power Corporation (KEPCO) is planning to apply an Eco Gas Insulated Switchgear (E-GIS) that does not use SF6. Accordingly, an environmentally friendly treatment of wasted SF6 is required. The KEPCO Research Institute (KEPRI) demonstrated a commercial-scale decomposition facility for treating a significant amount of high-purity SF6 discharged from waste electrical facilities in South Korea. This study conducted process characteristics tests of the SF6 decomposition facility to verify essential performance, such as the destruction removal efficiency (DRE) and the air pollutant concentrations at the exit. As a result, at a decomposition temperature of 1000 °C, the DRE exceeded 95%, and the air pollutant (HF, SO2, NOx, CO) concentrations at the exit were 0, 1, 30, and 7 ppm or less, respectively, exhibiting highly stable results. Furthermore, critical variable tests were conducted on the SF6 feed rate and decomposition temperature to identify optimal operating conditions. Results showed that the DRE exceeded 97% even with a stepwise increase in the SF6 feed rate to 10–50 LPM (65 ∼ 326 g/min). We confirmed that there was a slight decrease in DRE as the decomposition temperature decreased, but this did not influence the DRE significantly. The air pollutant concentrations were also lower than the legal standard. In particular, it reduced NOx emission to the environment by approximately 90%. Based on the performance test results, the operating conditions of the destruction temperature exceeding 980 °C and the pH range of neutralized water of 9–11 were derived, thus, it confirmed we can use the KEPCO's SF6 decomposition facility to commercialize the wasted SF6 treatment. Discharging wasted SF6 in an eco-friendly manner, based on the findings of this study, is expected to contribute to carbon neutrality.